Erratum: Action of Ganoderma lucidum mycelial growth filtrates on Erysiphe diffusa and embryotoxicity assessment in a chicken embryo model - da Cruz, Mycheli P.; Larentis, Lucas T.; Vismara, Edgar de S.; Vismara, Lilian de S.; Freitas, Patricia F. de; Mazaro, Sérgio M. (Acta Biologica Szegediensis, 2022)
Erratum